ANALISIS PELAKSANAAN PROGRAM PIDATO EMPAT BAHASA DALAM PENGUATAN PENDIDIKAN KARAKTER KEISLAMAN DI SDIT AT-TAQWA GRABAG - Halimatusa'diyah; Muhammad Nazil Iqdam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research explores the implementation of the Four-Language Speech Program (Pidato Empat Bahasa/PPEB) at SDIT At-Taqwa Grabag in reinforcing Islamic character education among students. Employing a qualitative case study approach and guided by the CIPP evaluation model (Context, Input, Process, Product), data were gathered through interviews, observations, and document analysis. The findings indicate that the PPEB program aligns with the school's vision of developing independent, high-achieving, and devout individuals. Teachers' mentoring, student involvement, and thematic content based on Islamic values support character formation. Students demonstrate increased confidence, responsibility, and politeness, although some challenges remain in terms of equal participation and the supporting infrastructure. The program has contributed significantly to developing students' critical communication skills and internalizing Islamic values in a structured manner. The PPEB also supports the actualization of the Pancasila Student Profile dimensions. The study recommends the development of standardized assessment rubrics, digital speech script archives, and continuous teacher training to optimize the program’s impact.